Evaluating Human Immunodeficiency Virus (HIV) Neuropathogenesis on HIV -Associated Neurocognitive Disorder (HAND): Role of Virology, Cellular and Immunology Aspects - Purbasari, Bethasiwi (Syntax Literate, 2024)
Human Immunodeficiency Virus (HIV) became a worldwide pandemic with a global prevalence of 36.9 million in 2014. One of the neurological complications of HIV infection is HIV-associated neurocognitive disorder (HAND). The administration of antiretroviral (ARV) therapy to HIV patients in general contributed to lowering HIV mortality and morbidity. However, ARV therapy did not provide complete protection for neurons. The cumulative prevalence of severe HAND in the lifetime of HIV patients is estimated to be 15%. HAND is classified into three categories: asymptomatic neurocognitive impairment (ANI), mild neurocognitive disorder (MND), and HIV-associated dementia (HAD). HAND remains a significant cause of morbidity in HIV patients. Recent findings on research using animal models have shown new concept development, both viral and cellular-related, on HAND neuropathogenesis, including other clinical factors contributing to HAND progression. Factors contributing to HAND neuropathogenesis consist of the cellular aspect, shown by the role of macrophages and astrocytes, and the viral aspect, shown by the role of neurotoxic HIV proteins and inflammatory molecules. HAND progression comprised chronic neuroinflammation, postsynaptic density decrements, and neurogenesis impairment. A better understanding of HAND neuropathogenesis will increase the optimization of HAND therapy.